Reproducible diagnosis of chronic lymphocytic leukemia by flow cytometry: An European Research Initiative on CLL (ERIC) & European Society for Clinical Cell Analysis (ESCCA) Harmonisation project. Issue 1 (17th January 2018) - Rawstron, Andy C.; Kreuzer, Karl‐Anton; Soosapilla, Asha; Spacek, Martin; Stehlikova, Olga; Gambell, Peter; McIver‐Brown, Neil; Villamor, Neus; Psarra, Katherina; Arroz, Maria; Milani, Raffaella; de la Serna, Javier; et al.
Abstract : The diagnostic criteria for CLL rely on morphology and immunophenotype. Current approaches have limitations affecting reproducibility and there is no consensus on the role of new markers. The aim of this project was to identify reproducible criteria and consensus on markers recommended for the diagnosis of CLL. ERIC/ESCCA members classified 14 of 35 potential markers as "required" or "recommended" for CLL diagnosis, consensus being defined as >75% and >50% agreement, respectively. An approach to validate "required" markers using normal peripheral blood was developed. Responses were received from 150 participants with a diagnostic workload >20 CLL cases per week in 23/150 (15%), 5–20 in 82/150 (55%), and <5 cases per week in 45/150 (30%). The consensus for "required" diagnostic markers included: CD19, CD5, CD20, CD23, Kappa, and Lambda. "Recommended" markers potentially useful for differential diagnosis were: CD43, CD79b, CD81, CD200, CD10, and ROR1. Reproducible criteria for component reagents were assessed retrospectively in 14, 643 cases from 13 different centers and showed >97% concordance with current approaches. A pilot study to validate staining quality was completed in 11 centers. Markers considered as "required" for the diagnosis of CLL by the participants in this study (CD19, CD5, CD20, CD23, Kappa, and Lambda) are consistent with current diagnostic criteria and practice. Importantly, a reproducible approach to validate and apply these markers in individual laboratories has been identified. Finally, a consensus "recommended" panel of markers to refine diagnosis in borderline cases (CD43, CD79b, CD81, CD200, CD10, and ROR1) has been defined and will be prospectively evaluated. © 2017 International Clinical Cytometry Society